Análise das estratégias de marcas em fornecedores de marcas próprias: estudo multicasos em fabricantes de produtos lácteos - Rezende, Sônia Regina Gouvêa (2013)
Researches confirm the importance of studying brands and all the decisions involved in their strategies, including analysis of manufacturers, distributors and consumers (KELLER, 2006; FISCHER et al, 2012). Competition has increased and different companies and brands are available. To stand out among so many options, Porter (1997) suggests companies adopt strategies to differentiate themselves from competition making them unique and bringing competitive advantages over competitors. In this context, it is relevant to study brand strategies from manufacturers´ point of view, particularly private label suppliers, as reported by different authors (PIATO, 2006; OUBINA et al, 2006; GOMEZ, BENITO, 2008; YOKOYAMA, 2010; ALTINTAS et al, 2010; GROZNIK, HEESE, 2010; CHEN et al, 2010; DABIJA, 2011). Private labels present a presumed paradox: competition and partnership (OUBINA, RUBIO, YAGUE, 2006; LIU, LIU, LIN, 2008; LIU, CHEN, CHEN 2011; DABIJA, 2011; OLSON, 2011 and 2012). Therefore, this study aims at answering the question: how is the decision to produce private labels included in dairy manufacturers´ brand strategies? To achieve this purpose, competitive and brand strategies are studied, as well as the reasons to produce private labels, identifying advantages and disadvantages of these products. The process and criteria for selecting and evaluating private label suppliers are also presented. Thus, a qualitative study was developed. Semi-structured interviews were conducted with four Brazilian companies that produce both national and private labels. The research protocol also included a non-participant observation in these companies to identify and compare their competitive strategies. From the theoretical background, seven propositions were developed to help achieve the objectives proposed. As suggested by Eisenhardt (1989), four private label suppliers were studied. The decision to develop a multicase study was also due to take into account different private label products, each one with its specificities (YIN, 2006). During this research, interviews with different actors in the selected companies were developed. After choosing and contacting the suppliers, the manager responsible for private labels in each manufacturer indicated the units and actors in essential functions in different hierarchical levels to be interviewed. It is important to mention that the interviewed actors were all involved in the decision to supply private labels. Dairy products were chosen for this study due to its performance in Brazil (ABMAPRO, 2011; ACNielsen, 2012). The analysis of the research corpus, through data triangulation (YIN, 2006), made it possible to verify an interaction between the various sources of evidence obtained. From the comparative analysis of the four companies studied, it was possible to present the convergence points regarding the analysis variables. Results indicate that, despite the disadvantages mentioned, supplying private labels may provide growth opportunities with continuous improvements in issues such as sales volume, larger market reach, economies of scale, improvements in existing processes and emphasis on learning, making these companies more competitive in their industries and giving them the opportunity to achieve higher levels of performance. It was possible to identify that private label is considered differentiation towards competition. Situations not yet described in the literature were also identified which may indicate specific features of the Brazilian market. The main contribution of this study is to present the motivating factors, advantages and disadvantages of providing private labels from the point of view of dairy products´ manufacturers.